Issues and Challenges of Pertashop Business: Analysis of Potential Bankruptcy From an Accounting Perspective - Halpiah, Halpiah; Utami, Karina Juniarti (Universitas Pendidikan Indonesia, 2025)
The purpose of this research is to find out how to assess the potential for Pertashop bankruptcy from an accounting perspective, analyze the potential for Pertashop bankruptcy on Lombok Island, and find out the bankruptcy prevention efforts made by Pertashop business actors. The method uses a qualitative case study approach on Lombok Island. In-depth interviews with 6 key informants (5 operators and 1 Pertashop supervisor) and conducting field observations conducted in 5 districts/cities on Lombok Island. The data is processed by creating a Pertashop bankruptcy prediction model. By implementing a bankruptcy prevention strategy that can be detected and prevented through timely intervention. This can be done by using 3 accounting perspective approaches: (1) financial accounting, recording simple financial reports; (2) cost accounting, Prestashop owners do not have cost standardization; (3) management accounting, leading to decision making when ordering fuel distribution. Local governments can design incentive policies and simplify the PBG (Building Approval) and SLF (Certificate of Functional Worthiness) licensing processes to support the sustainability of Pertashop in remote areas. Academically, this study was made to develop a specific bankruptcy prediction model for the BBM distribution partnership business that can be replicated and developed further. The novelty of this study uses 3 accounting perspectives in analyzing pertashop bankruptcy, namely financial accounting, cost accounting, and management accounting. Pertashops that apply the basic principles of the three accounting perspectives have a much higher survival rate and better financial performance than those that only rely on intuitive management.